Effects of Different Root Weights and Boron Fertilization on Plant and Siliqua Characteristics, Seed Yield, Germination and Emergence in Radish (Raphanus sativus L.) - Mihriban Namlı; Pınar Adıgüzel; İlknur Solmaz (Turkish Journal of Agriculture: Food Science and Technology)
In this experiment the effects of different root weights (50-99, 100-149, 150-199, 200-250 g) and increasing doses of boron application to soil (0, 100, 200, 300 g/da) on plant, siliqua, characteristics, and seed yield, germination and emergence in radish were investigated. In this research ‘‘Ç.Ü. Seleksiyon No:2’ radish genotype was used as plant material which developed by selection breeding method at Cukurova University, Faculty of Agriculture, Department of Horticulture. The experiment was carried out in open field and greenhouse conditions in 2017-2018 and 2018-2019. Radish roots were grown in an open field. Roots harvested for seed production were classified according to their weight and transferred to pots in the greenhouse. In this study, plant length (cm) plant diameter (mm), number of leaves (number/plant), number of siliquas (number/plant), siliqua length and width (mm), number of seeds (number/siliqua), 1000 seed weight (g), seed yield (g/plant), seed germination (%) and seed emergency (%) were analysed. According to the results of the two-year research, positive effects of increasing root weight were observed on the parameters measured in the plants, while the application of boron at different doses was found to be significant only in terms of the number of leaves. In terms of siliqua and seed characteristics, it was revealed that the increase in the root weight and applied boron dose was not effective except the increase in seed yield. Although seed germination was not affected by the applications, the best results were obtained from the application of 200 g/da boron at seedling emergence.